Walking and Bicycling Suitability Assessment at IIUM Pagoh Campus - Ahmad Redzuan, Muhammad Iswan Quzaimy; Sabarudin, Nur Syuhada Aisha; Mohd Rizan, Tuah Mikail Redza; Mohd Erwan Sanik, (Multidisciplinary Applied Research and Innovation, 2024)
There are two options for these students to go to their campus from their residential college which are by walking/bicycling or by using a provided bus. The aim of this research was to determine if a location or route is appropriate for biking and walking using WABSA and interview with some IIUM students. In order to conduct this studies, the road was observed according to WABSA Project Walking Suitability Assessment Form and Bicycling Suitability Assessment Form (adapted from N. Eddy) and every section has been observed. From the data, the some section from the road was not suitable for walking or cycling. This shows the fact that there is no road facilities special for walking and bicycling can be the main fact active transportation are rarely used among students.